Accelerating the manufacturing of HIV Env protein vaccines for early phase clinical evaluation - Michael N. Pensiero (npj Vaccines)
This commentary discusses the benefits in terms of time savings and reduced costs of goods in using transient electroporation and immuno-affinity purification as an alternative to the traditional manufacturing approaches for the CGMP manufacturing of HIV Envelope protein immunogens for use in investigational clinical studies. The companion manuscript by Bale et al. describes in detail this approach for CGMP manufacture and analytical evaluation of a near-native HIV envelope timer.